FAKTOR PREDIKTOR TERAPI AKUPUNKTUR PADA PASIEN KELEMAHAN ANGGOTA GERAK POST STROKE ISKEMIK AKUT YANG MEMPENGARUHI SKOR BARTHEL INDEX : LITERATURE REVIEW - Elies Fitriani; Maria Anastasia Darmawan; Nirawan Putranto; Adiningsih Srilestari (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
Introduction: Stroke is a major health problem that has a significant impact on quality of life and disability in carrying out daily work. Acupuncture play a role in the stroke rehabilitation through serotonin reuptake inhibitors and a series of local, segmental and central mechanisms. Several RCTs have proven that there is a significant effect of acupuncture in stroke therapy in acute and subacute ischemic stroke. However, most studies use small sample sizes and weak methodology. Method: This article is a literature review which aims to determine the predictor factors that influence the success of acupuncture therapy in patients with limb weakness after acute ischemic stroke. The search was carried out using databases from Pubmed, Cochrane and Embase which were then included in appropriate journals following the PRISMA flowchart to obtain 4 reviewed journals. Result: Factors that influence the success of acupuncture therapy in post-stroke patients include age, gender, previous medical history, comorbidities, the patient's clinical condition when initially entering treatment, the course of the disease, and the severity of the infarction. Conclusion: With minimal side effects, acupuncture therapy for acute ischemic stroke can be recommended as an adjuvant therapy for acute ischemic stroke. Research involving a larger number of participants with better methodology is needed to prove the effectiveness of acupuncture and its predictor factors for post-stroke limb weakness. Keywords: acupunture, Barthel Index, post stroke rehabilitation